PENINGKATAN KOMPETENSI GURU DALAM PENILAIAN PEMBELAJARAN MELALUI PENYUSUNAN DIGITAL STUDENTS’ WORKSHEET - Nika Sintesa; Siti Yulaikhah (Pusat Riset dan Inovasi Nasional, 2022)
Digital students' worksheets or interactive worksheets are one of the steps in applying technology in learning and assessment. Improving the skills of teachers in designing and creating digital Students' worksheets will be very beneficial for the teacher's self-development and improving the quality of learning in the classroom. The learning process during the pandemic can no longer be carried out offline or offline. It is necessary to assist the preparation of DSW by the teacher and upload it on liveworksheet.com so that in activity-based and student-centered learning, it will be able to assist in providing understanding of the material. Teachers as the frontline in education must swiftly and responsively master the use of virtual face-to-face applications, learning media and online assessments. The subjects of the study were subject teachers at SMP Negeri 2 Depok totaling 48 people. This activity must continue to be developed and implemented so that the results will be more visible and foster a changing friendly culture, meaning that teachers are more friendly with the changes that occur in the world of education. requires mastery of technology to facilitate the distance learning process. Improved skills of 47 teachers (97.92%). For DSW students, it can be used as learning to be active and can have an independent attitude and responsibility because the exercises they do come from the teacher and can be accessed anywhere, not limited by space and time and can be done repeatedly. The results of the study were 48 teachers (100%) listed KD on their DSW sheet, the options on multiple choice questions functioned (93.75%), the drag and drop button function was successfully executed (93.75%) and the join with arrow functioned (97.92%) . All material delivery through virtual or virtual classes.